Adaptation of R2B strain of Newcastle disease virus in vero cells - JOSHI, NAMITA; GARG, S K; CHANDRA, RAJESH; RAO, V D P (The Indian Journal of Animal Sciences, 2014)
In quest of a cell culture adapted vaccine strain for Newcastle disease (ND), the R2B strain virus (NDV) was propagated in vero cells. The growth and adaptation of virus were assessed by haemagglutination (HA) and infectivity titres and by study of cytopathic effects (CPE). The virus adapted well to vero cells and produced characteristic cytopathic effects like formation of syncytia, stellate cells, cytoplasmic vacuolation and intracytoplasmic inclusion bodies. With the increase in passage level, the infectivity titre of virud increased 'gradually, but the HA titre decreased. The pathogenicity indices revealed reduction in the virulence of virus after adaptation to vero cells.